The influence of sodium on the point defect characteristics in off stoichiometric CuInSe2. (November 2016) - Stephan, Christiane; Greiner, Dieter; Schorr, Susan; Kaufmann, Christian A.
Abstract: The device performance of polycrystalline chalcogenide thin film solar cells is strongly influenced by different kinds of defects within the material. The presence of sodium or other alkali metals like potassium during the deposition process is well known to influence the electronic properties of the solar cell and thus to improve the efficiency of the final device. Structural analysis of neutron powder diffraction data collected at low temperatures and subsequent profile analysis by the LeBail and Rietveld method demonstrates the impact of sodium on the point defect characteristics in off stoichiometric CuInSe2 . The analyzed materials are powder and thin film solar absorber material with addition of NaF and free of sodium. It is illustrated, the so called "sodium effect" cannot be reduced to one single origin. A range of effects, the reduction of InCu donors with a followed increase of VCu acceptors is possible. The main effect is an increased ordered character of the chalcopyrite crystal structure at off stoichiometric composition, when containing sodium. Highlights: Secondary defect phase in thin film material was observed by neutron diffraction. "Sodium-effect" cannot be reduced to one single origin. Differences in structural properties are small between samples with and without Na.